1995
DOI: 10.2307/591850
|View full text |Cite
|
Sign up to set email alerts
|

Five Feminist Myths about Women's Employment

Abstract: Feminist sociology has contributed substantial revisions to theory, especially in the sociology of work and employment. But it is also creating new feminist myths to replace the old patriarchal myths about women's attitudes and behaviour. Five feminist myths about women's employment are discussed whose acceptance as fact is not damaged by being demonstrably untrue. Arguably the most pervasive is the myth of rising female employment. The myth that women's work commitment is the same as that of men is often addu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
180
1
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(197 citation statements)
references
References 8 publications
5
180
1
8
Order By: Relevance
“…The second group consists of women who prioritise their homemaker role over their occupational role and are mainly represented in lower paid and part-time work roles. Hakim (1995) also suggested that both part-time workers and women who are not in paid employment can be viewed as prioritising the domestic sphere above paid employment.…”
Section: Attitudes Towards Work and Motherhood Held By Working And Nomentioning
confidence: 99%
See 1 more Smart Citation
“…The second group consists of women who prioritise their homemaker role over their occupational role and are mainly represented in lower paid and part-time work roles. Hakim (1995) also suggested that both part-time workers and women who are not in paid employment can be viewed as prioritising the domestic sphere above paid employment.…”
Section: Attitudes Towards Work and Motherhood Held By Working And Nomentioning
confidence: 99%
“…The aim of the present study is to compare attitudes towards motherhood and work in mothers who work full-time, part-time and those who do no paid work. Hakim (1991Hakim ( 1995 originally suggested that women might be divided into two groups, which represent personal choices about work and motherhood.…”
Section: Attitudes Towards Work and Motherhood Held By Working And Nomentioning
confidence: 99%
“…Indeed, the 'boundaryless' career (Arthur and Rousseau 1996) emphasises the move away from dependence on an organisational setting for the career. This causes difficulties when applied to professional work which demands a certain level of commitment not required by other occupations with lower level entry qualifications (Hakim, 1995(Hakim, , 1996 and tends to translate into longer working hours (Epstein et a,l 1999). There are few professions in which part-time work or any deviation from the 'traditional' working patterns is commonplace in spite of many commentators suggesting that the flexible patterns of working adopted by women could be advantageous and applicable in a much wider context (Sullivan, 1999;Mallon and Cohen, 2001;Shaw et al, 2000).…”
Section: Women and Professional Careermentioning
confidence: 99%
“…There is an implicit assumption that selfemployment, in the form of sole practitioner, principal in practice or on a labour-only basis, exists primarily as a solution to the problems of juggling family and career (Goffee and Scase 1985;Hakim 1995Hakim , 1996Crompton and Le Feuvre 1996). However, meeting family responsibilities was not the only reason for becoming a sole practitioner as four of the nine sole practitioners were childless and the other two formed their practices after their children were grown up.…”
Section: Choice and Diversity In Women's Careers: A New Perspective?mentioning
confidence: 99%